A Note on Surplus Content. Issue 2 (3rd April 2017) - Steinberg, Alexander
ABSTRACT: In the target article, Stephen Yablo appeals crucially to the notion of surplus content. But when he does so, it is by appeal to the notion of mathematical addition and subtraction. In this commentary, I argue that the analogy with mathematical subtraction is underdeveloped and potentially misleading.